Results of Cataract Extraction in Patients with Corneal Opacity - E. A. Ivachev; E. V. Anisimova; I. P. Denisova (Oftalʹmologiâ, 2019)
Purpose. To evaluate the effectiveness of cataract extraction in patients with varying degrees of corneal opacity.Patients and methods. We performed cataract extraction with implantation of the intraocular lenses of 14 eyes (9 patients) with varying degree of corneal opacity. The causes of corneal opacities were: keratitis in anamnesis — 6 cases, the result of wearing soft contact lenses — 2 eyes, eye injury — 2, the outcome of dermatitis of unspecified genesis with eye damage — 3, perforation of the corneal ulcer — 1 case. In 9 eyes, opacity of the cornea occupied the optic part of the cornea, in 5 cases, the opacity of the cornea was in the paraoptic zone. The middle uncorrected visual acuity of all cases is 0.05 ± 0.03, and the middle best corrected visual acuity is 0.14 ± 0.07. The phacoemulsification of the cataract with implantation of the intraocular lens was performed for all the patients.Results. There were no complications during the operation, in the early and late postoperative periods. As a result of cataract extraction, all patients, regardless of the degree of cornea opacity, noted vision improvement. On the first day after the operation, the middle best corrected visual acuity was 0.06 ± 0.02 in 4 eyes, in 10 cases the middle best corrected visual acuity was 0.09 ± 0.03. The middle best corrected visual acuity 7 days after the surgery was 0.31 ± 0.07. After 6 months of observation of patients with corneal opacity after phacoemulsification of the cataract with implantation of the intraocular lens, the most corrected visual acuity was 0.27 ± 0.19.Conclusions. All patients with corneal opacity of varying degrees of intensity after cataract extraction noted improved vision. The central location of the opacity of the cornea significantly reduced visual acuity, and paraoptic — influenced the vision to a lesser extent. The degree of cornea turbidity was also affected the initial visual acuity — the more clouding and the depth of the cornea, the lower the vision. The result of the lens extraction also depended on the maturity of the cataract — with a more turbid lens the result was higher in relation to preoperative indices.